2020
DOI: 10.1155/2020/9796019
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Structured Education on Glycemic Control and Psychological Outcomes in Adolescent and Adult Patients with Type 1 Diabetes: A Systematic Review and Meta-Analysis

Abstract: Aim. This systematic review aimed at investigating the effectiveness of structured education (SE) in improving glycemic control and psychological outcomes in adolescent and adult patients with type 1 diabetes. Methods. Electronic databases (EMBASE, Medline, PubMed, and the Cochrane Library) and the reference lists of included studies were searched from the beginning of the database through April 2019. Randomized controlled trials comparing SE with a control condition and reporting a change in glycosylated hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Even so, as this same study confesses, meta-analyses in the USA found that psychoeducational interventions can improve HbA1c levels by up to half a percentage point, in addition to other psychological and educational benefits (Armour et al, 2005;Winkley et al, 2006). Another study argues that although no evidence of significant improvements in HbA1c levels was found in their meta-analysis for the adolescent population after structured education, there was evidence for the adult population (Liu et al, 2020), though a reduction in vascular complications was found in the adult population with T1D (Menezes et al, 2016).…”
Section: Contrasting Positions On the Effectiveness Of Educational Or Psychoeducational Interventionsmentioning
confidence: 91%
“…Even so, as this same study confesses, meta-analyses in the USA found that psychoeducational interventions can improve HbA1c levels by up to half a percentage point, in addition to other psychological and educational benefits (Armour et al, 2005;Winkley et al, 2006). Another study argues that although no evidence of significant improvements in HbA1c levels was found in their meta-analysis for the adolescent population after structured education, there was evidence for the adult population (Liu et al, 2020), though a reduction in vascular complications was found in the adult population with T1D (Menezes et al, 2016).…”
Section: Contrasting Positions On the Effectiveness Of Educational Or Psychoeducational Interventionsmentioning
confidence: 91%
“…46,47 However, a meta-analysis concluded that SE had no significant effect on glycaemic control, diabetes self-efficacy, or QoL in adolescents with T1D. 48 They attributed it to lack of maturity and lack of knowledge and understanding of the disease and its complications as well as the therapeutic regimens of T1D. Also, most of these SE programmes focused primarily on carbohydrate counting and insulin adjustment which may be difficult for adolescents to comprehend.…”
Section: Solutionmentioning
confidence: 99%
“…In particular, the highest quality educational approach is structured education, a program with a clear purpose and flexible content, designed to meet the clinical and psychological needs of the patient while adapting to their socio-cultural context [ 23 ].…”
Section: Discussionmentioning
confidence: 99%